Exploring the Potential of Palm Oil Fuel Ash (POFA) in EMI Shielding Effectiveness / Narong Oh Lai Ching...[et al.] - Narong Oh, Lai Ching; Sia, Chee Kiong; Zainudin, Azlan; Yee, See Khee (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The issue of environmental pollution resulting from disposal of palm oil fuel ash (POFA) in Malaysia has drawn the interest of many researchers. It is reported that it can be incorporated into the cement based composite as the electromagnetic field (EMF) absorber to reduce the EMI radiation. This paper explores the performance of each layer of POFA in EMI shielding. In this work, the POFA is split into four layers after the stirring process in the water. The first layer of the POFA tends to float as based on the SEM morphology, it possesses high porosity compared to other layers. Based on the transmission measurement using a network analyser, it is found that the 7 mm of layer 1 which contains 85.89 wt.% of carbon can provide shielding effectiveness (SE) of -25.76dB in between 50 MHz to 2 GHz. Besides the high carbon content, the porosity of layer 1 enhances its capability as shielding material too.